Chloride penetration resistance and frost resistance of fiber reinforced expansive self-consolidating concrete. (15th January 2018) - Cao, Qi; Gao, Quanqing; Gao, Rongxiong; Jia, Jinqing
Highlights: Chloride penetration and frost resistance of fiber reinforced ESCC were studied. Increasing fiber factor enhances chloride penetration resistance along the depth. The RDME of fiber reinforced ESCC decreases with the increasing fiber content. Increase of fiber content decreases the speed of mass change of the specimens. Abstract: The objective of this paper is to investigate the chloride penetration resistance and frost resistance of fiber reinforced expansive self-consolidating concrete (ESCC). Fibers and expansive agent were used to decrease shrinkage, control cracks and enhance microstructure of the concrete. Steel fibers with three volume fractions (0.25%, 0.50% and 0.75%) of the total volume of concrete and monofilament polypropylene fibers with two volume fractions (0.05%, 0.10%) were used in the test. This study established levels of chloride penetration of fiber reinforced ESCC. The frost resistance was determined by rapid freezing and thawing test. Results indicated that PP shows more sensitivity on slump flow than SF but less impact on T500. Chloride content increased with the incorporation and increase of fibers at depths less than 17.5 mm. However, chloride penetration resistance along the depth was enhanced with increasing fiber factor. SF0.50PP0.05 exhibits the best chloride penetration resistance, and SF with a volume fraction of 0.50% and PP with a volume fraction of 0.05% show mutual beneficial effect on the chloride penetration resistance of ESCC. The relative dynamic modulus of elasticity (RDME) of ESCC in the presence of fibers decreased slightly when compared with ESCC in the absence of fibers, and decreased with the increasing fiber factor. It also shows that the increase of fiber content decreased the speed of surface spalling of the specimens as well as the mass change.